2020
DOI: 10.1155/2020/7059209
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Characteristics of Helicopter with Ducted Fan Tail Rotor in Hover under Low-Speed Crosswind

Abstract: The tail rotor of a helicopter operating under low-speed crosswind undergoes highly complex flow due to the interaction between the main rotor, fuselage, and tail rotor system. In this study, numerical simulations have been conducted on the complete configuration of a helicopter with a ducted fan tail rotor system (comprising a main rotor, ducted fan tail rotor, fuselage, and empennage) to analyze the wake interaction in hovering flight under various crosswind directions. The flow characteristics around the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The characterization of the MR wake using overset mesh technology is a time-consuming task due to the hole cutting process and data transfer between donor and acceptor cells at each time step [25,26]. The actuator disk approach has been used to perform successful rotor wake simulations in MR-fuselage [27,28], MR-TR [22], MR-tail boom [29], and MR-lateral rotor and wing [30,31] interaction calculations. Several researchers have demonstrated that one characteristic feature of the MR disc vortices wake is well-known coherent supervortices, as the blade tip vortices roll up in the downstream [32].…”
Section: Numerical Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The characterization of the MR wake using overset mesh technology is a time-consuming task due to the hole cutting process and data transfer between donor and acceptor cells at each time step [25,26]. The actuator disk approach has been used to perform successful rotor wake simulations in MR-fuselage [27,28], MR-TR [22], MR-tail boom [29], and MR-lateral rotor and wing [30,31] interaction calculations. Several researchers have demonstrated that one characteristic feature of the MR disc vortices wake is well-known coherent supervortices, as the blade tip vortices roll up in the downstream [32].…”
Section: Numerical Methodologymentioning
confidence: 99%
“…Given that the vertical fin has a limited lift in low flight speed conditions, the yaw stability could be mainly detected on the curve slope of the TR thrust versus the wind azimuth. The yaw stability characteristics that were detected with this scheme have been widely applied in previous wind tunnel [15] and numerical simulation [22,24] studies.…”
Section: Test Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…They adopted CFD to calculate the flow field and tail rotor performance for both hover and lateral flight conditions. Many researchers are interested in the flow field and the location of the vortex core under different flight conditions [16][17][18]. The prediction method is the key factor for ducted rotor noise analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the complex shafting structural designs of helicopters, any slight changes in the relative positions of shafting will lead to changes in the transmission characteristics of the entire transmission system, which will accelerate the wear of support bearings, shorten the service life of the bearings, and greatly impact the tooth surface friction at the gear meshing. As a result, vibration impacts will be produced which will negatively affect the performances of the transmission systems [11,12]. Due to the aforementioned tendencies, the transmission systems of helicopters may be subjected to additional excitation force, which will significantly reduce the working life of the transmission systems.…”
Section: Introductionsmentioning
confidence: 99%